Regulation of Legal Protection for Notaries in Performing Official Duties to Ensure Legal Certainty and Justice - Agnes Nova Randomis (Ridwan Institute, 2025)
Notaries, as public officials authorized to draft authentic deeds, hold an important position within the Indonesian legal system. However, in practice, notaries often encounter legal issues arising from the execution of their duties, whether in criminal, civil, or professional ethical contexts. This paper aims to analyze the regulation of legal protection for notaries in performing official duties to ensure legal certainty and justice and to propose normative reconstruction ideas aligned with the principles of legal certainty and justice. The research method employed is a normative approach, utilizing analyses of laws and regulations, legal doctrines, and case studies. The findings indicate that the Regulation of Legal Protection for Notaries in Performing Official Duties to Ensure Legal Certainty and Justice under Law Number 2 of 2014, amending Law Number 30 of 2004 concerning the Notary Position, remains partial and fails to provide comprehensive protection. Policy reconstruction is therefore necessary by strengthening legal protection norms that encompass aspects of office accountability, equitable supervision mechanisms, and limitations on law enforcement intervention. Consequently, enhanced legal protection for notaries will better guarantee legal certainty and justice for all parties and the wider community.